Gender differences in the intention to get vaccinated against COVID-19: a systematic review and meta-analysis - Zintel, Stephanie; Flock, Charlotte; Arbogast, Anna Lisa; Forster, Alice; Von Wagner, Christian; Sieverding, Monika (Journal of public health, 2023)
We conducted a systematic review and meta-analysis to analyse gender differences in COVID-19 vaccination intentions.